Sb smelting alkaline waste residue-based mullite phase refractory material, preparation method and application thereof
Patent Information
- Application Number
- CN202611392287.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-09
- Publication Date
- 2026-10-16
AI Technical Summary
该工艺仍存在以下不足:反应温度高、能耗大,高温反应炉为间歇操作,每批次需停炉放渣,难以实现连续化大规模生产;且该工艺仅关注有价组分回收,对反应后产生的大量氧化钠碱渣缺乏有效的二次处置方案,其长期环境安全性有待验证
[0034] This invention provides a method for preparing refractory materials using alkaline waste residue from antimony smelting, along with the product and its application. Compared to existing technologies, this invention offers the following advantages:
Smart Images

Figure CN122916699A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of hazardous solid waste treatment and resource utilization, and particularly to the field of mullite-phase refractory materials based on antimony smelting alkaline waste slag, their preparation methods, and applications. Background Technology
[0002] Currently, over 95% of antimony smelting production utilizes pyrometallurgical processes, which generate a large amount of alkaline waste slag. During pyrometallurgical antimony smelting, sodium carbonate is added for oxidative refining to remove arsenic impurities from crude antimony, producing arsenic-containing, antimony-, and sodium-containing waste slag, known as arsenic-alkali slag. This slag has a high antimony content and is typically returned to the reverberatory furnace by smelting companies for antimony recovery. After antimony recovery, the remaining arsenic-alkali slag undergoes oxidative alkali leaching and magnesium ammonium precipitation treatment, followed by roasting to obtain another type of alkaline waste slag—magnesium-rich roasted slag. Its main components are magnesium oxide and magnesium pyroarsenate, along with certain amounts of sodium, silicon, and other components. Both types of waste slag are typical alkaline waste slags generated during antimony smelting, characterized by strong alkalinity, high salinity, and complex composition. Under open-air storage conditions, they are easily leached into surrounding soil and water bodies by rainwater, posing a potential threat to the ecological environment. Currently, alkaline waste slag is generally disposed of through stockpiling, but the stockpile volume has reached hundreds of thousands of tons, urgently requiring resource utilization.
[0003] Existing methods for treating alkaline waste residue from antimony smelting mainly include solidification and landfill, pyrometallurgy, and hydrometallurgy. While solidification and landfill are simple to operate, they pose a risk of long-term heavy metal leaching and consume significant land resources. Pyrometallurgy is energy-intensive, and arsenic may volatilize in gaseous form, causing secondary pollution. Hydrometallurgy offers relatively reliable treatment, but its process is lengthy, involves multiple separation steps, and generates large amounts of high-salinity wastewater, resulting in high subsequent treatment costs.
[0004] CN211036045U discloses an arsenic-alkali slag treatment system, which involves reacting arsenic-alkali slag with a reducing agent at a high temperature of 1250~1550℃, causing arsenic and antimony to escape in vapor form. After cooling and crystallization, crude arsenic is recovered, and sodium oxide alkali slag is produced at the bottom of the furnace. This process still has the following shortcomings: high reaction temperature and high energy consumption; the high-temperature reactor operates intermittently, requiring shutdown and slag discharge after each batch, making continuous large-scale production difficult; furthermore, this process only focuses on the recovery of valuable components and lacks an effective secondary disposal plan for the large amount of sodium oxide alkali slag generated after the reaction, and its long-term environmental safety needs to be verified.
[0005] CN109748526A discloses a process for the co-processing of arsenic-alkali slag in cement kilns. The process involves crushing the arsenic-alkali slag, adding it to siliceous raw materials and coal for high-temperature calcination, causing arsenic and antimony to sublimate and enter the flue gas. The calcined slag is then fed into a cement kiln for further incineration and solidification. Arsenic-containing and antimony-containing flue gas are used as raw materials for smelting metallic arsenic and antimony, respectively. Once the arsenic content in the sintered slag is below 0.5 mg / kg, it can be used as a cement raw material. However, in this patent, the amount of arsenic-alkali slag added to cement is only 0.5%~1%, and the final products are cement clinker and cement products. The arsenic-alkali slag needs to be dispersed in a large amount of cement substrate at a low dosage. Furthermore, this process is highly dependent on co-processing in cement kilns, and due to the geographical location and production scale of cement plants, it cannot achieve independent on-site disposal of arsenic-alkali slag. In addition, high-temperature incineration causes arsenic and antimony to sublimate and volatilize into the flue gas; if the flue gas treatment is improper or the system operation fluctuates, there is a risk of secondary pollution.
[0006] The methods described above all focus on the recovery of valuable components, but no effective resource utilization scheme has yet been developed for the end-of-life alkaline waste residues generated during the smelting process, especially newly generated waste residues such as magnesium-rich roasting slag. Meanwhile, the alkaline waste residues generated during antimony smelting have complex compositions and varied phases, and the properties of waste residues generated from different processes differ significantly. Therefore, there is an urgent need to develop a unified treatment technology applicable to various types of alkaline waste residues.
[0007] In recent years, research on the co-sintering of hazardous waste with raw materials such as clay to prepare refractory materials has attracted widespread attention. This method utilizes the stable crystalline phase and dense structure formed at high temperatures to fix heavy metals within the refractory matrix, thereby achieving the harmless and resource-based utilization of hazardous waste. However, the high content of sodium and magnesium salts in the alkaline waste residue from antimony smelting easily leads to the generation of excessive liquid phase during sintering, causing material deformation, foaming, and even melting, severely restricting the mechanical properties of refractory materials. Therefore, how to utilize the chemical composition characteristics of the alkaline waste residue from antimony smelting to prepare high-performance refractory materials through reasonable proportioning design and process control remains an urgent problem to be solved. Summary of the Invention
[0008] To address the problems existing in the prior art, the primary objective of this invention is to provide a method for preparing mullite-phase refractory materials based on antimony smelting alkaline waste slag, aiming to utilize the resource-based preparation of mullite-phase refractory materials from antimony smelting alkaline waste slag.
[0009] The second objective of this invention is to provide a mullite-phase refractory material based on antimony smelting alkaline waste slag prepared by the aforementioned method.
[0010] The third objective of this invention is to provide the application of the aforementioned antimony smelting alkaline waste slag-based mullite phase refractory material.
[0011] Antimony smelting alkaline waste mainly includes two typical types: arsenic-alkali slag and magnesium-rich roasted slag. Compared with conventional arsenic-containing waste (such as arsenic-iron slag and arsenic-calcium slag), antimony smelting alkaline waste has the following significant characteristics: First, its alkaline oxide content is extremely high—the Na2O content in arsenic-alkali slag is as high as 42.5 wt% or more, and the MgO content in magnesium-rich roasted slag is as high as 46 wt% or more—far higher than other arsenic-containing waste. This high alkalinity makes it very easy to generate an excess liquid phase during high-temperature sintering, leading to material deformation, foaming, and even melting, which seriously restricts the densification and mechanical property control of refractory materials. Second, arsenic mainly exists in the form of soluble sodium arsenate in arsenic-alkali slag or in the form of magnesium pyroarsenate in magnesium-rich roasted slag. Its migration ability in the aqueous environment is extremely strong, and arsenic has significant volatility at high temperatures. How to achieve in-situ fixation of arsenic during high-temperature sintering while avoiding its escape in gaseous form and causing secondary pollution is a technical problem that urgently needs to be solved in this field. Third, the Si / Al content in the alkaline waste residue from antimony smelting is extremely low, which deviates significantly from the stoichiometric ratio (3Al2O3·2SiO2) required for mullite, necessitating the introduction of high-alumina silicon raw materials for proportioning compensation.
[0012] To prepare mullite-phase refractory materials from alkaline waste residue of antimony smelting, the following technical challenges need to be addressed: (1) Selective generation and control of mullite crystal phase. In the high Na2O environment of arsenic-alkali slag, Na + It will preferentially react with Al2O3 and SiO2 to form low-melting-point nepheline (NaAlSiO4) and other phases, inhibiting the nucleation and growth of mullite; while in the high MgO environment of magnesium-rich roasted slag, Mg 2+ It will preferentially react with Al2O3 and SiO2 to form cordierite (Mg2Al4Si5O). 18 This competes with the target mullite. How to... + / Mg 2+The core technical challenge of this invention is to guide the preferential precipitation of mullite crystal phase under the existing competitive environment, while suppressing the large-scale generation of impurity phases such as nepheline and cordierite. (2) Synchronous solidification and anti-leaching stability of As / Sb. Arsenic and antimony coexist in the alkaline waste residue of antimony smelting, but their volatilization behavior at high temperature and compatibility with mullite lattice are different. How to achieve synchronous solid solution of As / Sb in mullite lattice and ensure that the leaching concentration is lower than the national standard limit (As≤5 mg / L) is the core requirement of environmental safety. (3) Control of excess liquid phase and structural stability. High Na2O / MgO content is prone to generating excess liquid phase during sintering. Although it is beneficial to densification, excess liquid phase will lead to abnormal growth of mullite grains, increased porosity and material creep. How to establish a precise balance between densification and overburning to ensure the high-temperature performance of refractory materials is a key problem of process control. (4) The adverse effects of fine waste residue particles and easy mudification on molding. The alkaline waste residue from antimony smelting has extremely fine particles that are easily muddied. During the molding process, this can lead to uneven density distribution and low strength in the green body, increasing the risk of uneven shrinkage and cracking during sintering.
[0013] To address the problems in the resource utilization of alkaline waste residue from antimony smelting for the preparation of mullite-phase refractory materials, this invention provides the following improvement:
[0014] A method for preparing a mullite phase refractory material based on antimony smelting alkaline waste slag involves mixing antimony smelting alkaline waste slag and kaolin in a weight ratio of 0.5:10 to 5:10, molding the mixture into a green body, and then calcining it at a temperature of 750 to 1250°C to obtain the antimony smelting alkaline waste slag based mullite phase refractory material.
[0015] This invention uses alkaline waste residue from antimony smelting and kaolin as raw materials. Based on the fluxing effect of sodium or magnesium salts in the waste residue and the phase transformation characteristics of kaolin at high temperatures, and by controlling the raw material ratio and sintering temperature, a dense refractory matrix with mullite as the main crystalline phase and a stable arsenic-antimony solid solution are simultaneously formed, creating a green and efficient refractory preparation process. High-temperature sintering is a mature material processing method, and the refractory materials prepared using this method have advantages such as high density, good mechanical properties, and low leaching toxicity of heavy metals. The solidified arsenic and antimony exist stably in the pentavalent form within the mullite lattice or dense glassy phase, with leaching concentrations far below standard limits. The entire preparation process utilizes widely available raw materials, is simple to operate, and produces no secondary pollution, achieving the harmless treatment and resource utilization of alkaline waste residue from antimony smelting. It is an environmentally friendly and advanced process.
[0016] The alkaline waste residue includes arsenic-alkali residue or magnesium-rich roasted residue.
[0017] The main physicochemical parameters of the arsenic-alkali slag are: Na2O content 42~45 wt%, As content 10~25 wt%, Sb content 2~11 wt%; further, Na2O content 42.5~43.5 wt%, As content 20~24 wt%, Sb content 5~7 wt%.
[0018] The main physicochemical parameters of the magnesium-rich roasted slag are: MgO content 46~50 wt%, Na2O content 7~10 wt%, As content 1~2.0 wt%, and Sb content 0.4~0.6 wt%.
[0019] The kaolin contains 35-40 wt% alumina and 45-50 wt% silicon dioxide. The kaolin contains <0.5 wt% Fe₂O₃ and <0.1 wt% K₂O + Na₂O. At high temperatures, the kaolin undergoes a phase transformation path from dehydroxylation to metakaolinite to mullite, resulting in a needle-like mullite crystal network structure, which is beneficial for improving the thermal shock resistance of refractory materials. Simultaneously, kaolin possesses good plasticity and binding properties, allowing for molding without the addition of additional binders, and exhibits high green strength.
[0020] Preferably, the particle size of the antimony smelting alkaline waste residue and kaolin is controlled to be below 100 mesh (i.e., particle size ≤ 74 μm).
[0021] Preferably, the alkaline waste residue and kaolin both include large particles and small particles in a weight ratio of 0.5 to 2:1, wherein the particle size of the large particles is 100 to 200 mesh (the material above 200 mesh and below 100 mesh sieve), and the particle size of the small particles is below 200 mesh (the material below 200 mesh sieve).
[0022] Preferred particle size control helps to further improve the synergy of co-calcination of alkaline waste residue and kaolin, helps to further enhance the phase and structure control of the prepared material, and helps to further improve its performance; the synergistic effect of particle size distribution and fluxing effect can obtain high-density products at lower sintering temperatures, avoiding over-burning and deformation caused by excessive liquid phase.
[0023] In this invention, the weight ratio of alkaline waste residue to kaolin can be 0.5:10, 1:10, 2:10, 3:10 or 4:10.
[0024] Preferably, the molding method is mechanical pressing, and the molding pressure is 10~20 MPa.
[0025] Preferably, the calcination atmosphere is an air atmosphere. In this invention, the calcination temperature can be 800℃, 1000℃, or 1200℃. The calcination time is 0.5 to 3 hours.
[0026] The roasting process includes a first roasting process at temperature T1, a second roasting process at temperature T2, and an annealing process at temperature T3.
[0027] Among them, temperature T1 is 1050~1150℃; temperature T2 is 50~100℃; temperature T3 is 750~850℃;
[0028] Preferably, the heat preservation time at temperature T1 is 0.4~1h; the heat preservation time at temperature T2 is 0.5~1.5h; and the heat preservation time at temperature T3 is 0.5~1.5h.
[0029] By controlling the nucleation and growth process of mullite in stages, annealing helps to release the thermal stress accumulated during sintering, while promoting the crystallization of the residual glass phase and improving the long-term thermal stability of the material.
[0030] The present invention also provides a mullite phase refractory material based on antimony smelting alkaline waste slag prepared by the above preparation method.
[0031] The antimony smelting alkaline waste slag-based mullite phase refractory material has an apparent porosity of not more than 15%, a compressive strength of not less than 50 MPa, a Mohs hardness of not less than 6, an arsenic leaching concentration of not more than 0.05 mg / L, and an antimony leaching concentration of not more than 0.03 mg / L.
[0032] The present invention also provides an application of the antimony smelting alkaline waste slag-based mullite phase refractory material prepared by the above preparation method, which is used to prepare refractory materials.
[0033] Beneficial effects:
[0034] This invention provides a method for preparing refractory materials using alkaline waste residue from antimony smelting, along with the product and its application. Compared to existing technologies, this invention offers the following advantages:
[0035] Firstly, in terms of environmental safety, this invention stabilizes and solidifies arsenic and antimony in the alkaline waste residue from antimony smelting within the mullite lattice and dense glass phase through high-temperature sintering. Arsenic and antimony mainly exist in the low-toxicity pentavalent form, significantly reducing the leaching concentration to far below the national standard limit. Furthermore, the leachate from the sintered refractory material has no toxic effect on plants, fundamentally solving the problem of the high toxicity and difficulty in safely disposing of alkaline waste residue from antimony smelting.
[0036] Secondly, in terms of resource utilization, this invention realizes the transformation of hazardous waste into high-value refractory materials. The resulting refractory material has mullite as the main crystalline phase, a dense structure, a compressive strength of over 50 MPa, a Mohs hardness of not less than 6, and an apparent porosity of not more than 15%. It has good mechanical properties and durability and can be used as environmentally friendly bricks, curing materials, or building aggregates.
[0037] Third, in terms of process, this invention employs a simple mixing, pressing, and high-temperature sintering process, which is easy to operate, uses inexpensive raw materials, requires no complex separation and purification steps, does not generate secondary pollution, has controllable energy consumption, and is easy to industrialize. In summary, this invention achieves the harmless treatment and high-value utilization of alkaline waste residue from antimony smelting, possessing environmental, economic, and social benefits. Attached Figure Description
[0038] Figure 1 The microstructure characterization diagrams are shown for the refractory material prepared in the embodiments of the present invention and the comparative example (alkaline waste smelting without antimony under the same process), wherein: Figure 1 (a) is a SEM image of the refractory sample (A-10 / 1-1200) prepared in Example 1 at a scale of 5 µm; Figure 1 (b) is a SEM image of the refractory sample (M-10 / 1-1200) prepared in Example 2 at a scale of 5 µm; Figure 1 (c) is a SEM image of a refractory sample (K-1200) prepared without the addition of waste residue under the same process at a scale of 5 µm; Figure 1 (d) is the nitrogen adsorption-desorption isotherm for the corresponding sample, where Ads represents the adsorption process and Des represents the desorption process. Figure 1 (e) is the DFT pore size distribution diagram of the corresponding sample.
[0039] Figure 2 These are the XPS spectra of the refractory samples from the embodiments and comparative examples of the present invention, wherein: Figure 2 (a) is the high-resolution spectrum of Na 1s; Figure 2 (b) is the high-resolution spectrum of As 3d; Figure 2 (c) is the high-resolution spectrum of O 1s; Figure 2 (d) is the high-resolution spectrum of Mg 1s.
[0040] Figure 3 These are comparative images of the appearance of refractory cylinders sintered at 800℃, 1000℃, and 1200℃ according to embodiments of the present invention. Wherein: Figure 3 (a) Comparison of the appearance of refractory samples prepared with added arsenic-alkali slag; Figure 3 (b) Comparison of the appearance of refractory samples prepared by adding magnesium-rich roasted slag.
[0041] Figure 4 This is an XRD phase analysis diagram from an embodiment of the present invention. Wherein, Figure 4 (a) XRD patterns of the sample obtained in Example 1 at different sintering temperatures (room temperature, 800℃, 1000℃, 1200℃). Figure 4(b) XRD patterns of example samples with different mass ratios of arsenic-alkali slag to kaolin (10 / 0, 10 / 0.5, 10 / 1, 10 / 2, 10 / 3) after sintering at 1200℃.
[0042] Figure 5 This is a graph showing the relationship between the properties of refractory materials prepared at different sintering temperatures (800℃, 1000℃, 1200℃) and the mass ratio of antimony smelting alkaline waste slag (arsenic-alkali slag AAR / magnesium-rich roasted slag MRS) and kaolin in embodiments of the present invention. Figure 5 (a) is a graph showing the change in apparent porosity. Figure 5 (b) is a graph showing the change in bulk density. Figure 5 (c) is a graph showing the change in compressive strength. Figure 5 (d) is a graph showing the change in linear shrinkage rate.
[0043] Figure 6 The graph shows the concentrations of As(III), total As, and total Sb in the leachate of the original powder and the refractory materials prepared at different sintering temperatures (800℃, 1000℃, 1200℃) after soaking in deionized water in the embodiments of the present invention. Detailed Implementation
[0044] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0045] It should be noted that, unless otherwise specified, the following embodiments and features can be combined with each other. It should also be understood that the terminology used in the embodiments of this invention is for describing specific implementations and not for limiting the scope of protection of this invention.
[0046] Unless otherwise defined, all technical and scientific terms used in this invention are consistent with the prior art known to those skilled in the art and the description of this invention. This invention can also be implemented using any prior art methods, devices, and materials similar to or equivalent to those described, used, or made of materials in the embodiments of this invention. It should be understood by those skilled in the art that, as an explanation of this application, without affecting the actual understanding of the technical solutions of this application, "Binding Energy (eV)" can represent binding energy, "Intensity (au)" can represent intensity, and "Wavenumber (cm²)" can represent strength. -1"()" can be expressed as wavenumber, "Transmittance (%)" can be expressed as transmittance, "2 Theta (°)" can be expressed as diffraction angle, "dV / dW Pore Volume" can be expressed as micropore volume, "Quantity Adsorbed" can be expressed as adsorption amount, "Relative Pressure" can be expressed as relative pressure, "Apparent Porosity" can be expressed as apparent porosity, "Bulk Density" can be expressed as bulk density, "Compressive Strength" can be expressed as compressive strength, and "Linear Shrinkage" can be expressed as linear shrinkage rate.
[0047] When numerical ranges are given in the examples, it should be understood that, unless otherwise stated in the invention, both endpoints of each range and any value between the two endpoints may be used. Test methods in the following examples that do not specify specific conditions are generally performed under conventional conditions or as recommended by the respective manufacturers. Unless otherwise specified, all materials or reagents required in the following examples are commercially available.
[0048] To address the problems of unsafe disposal and high toxicity of existing antimony smelting alkaline waste residue, this invention provides a method for preparing refractory materials using antimony smelting alkaline waste residue, comprising the following steps:
[0049] Alkaline waste residue from antimony smelting is mixed with kaolin in a certain proportion to obtain a mixture; the mixture is pressed into shape to obtain a green body; the green body is sintered at high temperature to obtain a refractory material.
[0050] Specifically, the alkaline waste residue from antimony smelting includes arsenic-alkali slag and magnesium-rich roasted slag. Arsenic-alkali slag originates from hazardous solid waste generated during the oxidative refining processes for arsenic, sulfur, and iron removal in antimony refining. Its main components are sodium arsenate, sodium carbonate, and small amounts of antimony compounds. Magnesium-rich roasted slag is an alkaline waste residue obtained by oxidative alkali leaching and magnesium ammonium precipitation followed by roasting of arsenic-alkali slag. Its main components are magnesium oxide and magnesium pyroarsenate. The kaolin is soft kaolin with an alumina content of 35-37 wt% and a silicon oxide content of 48-50 wt%. Both the sodium salts in the arsenic-alkali slag and the magnesium salts in the magnesium-rich roasted slag can act as fluxes at high temperatures, promoting liquid-phase mass transfer and the growth of the mullite crystal phase, while simultaneously solidifying arsenic and antimony in pentavalent forms within the mullite lattice or dense glassy phase. Further, the solid antimony smelting alkaline waste slag is crushed, dried at 55-65℃ until the moisture evaporates, then ground and passed through a 200-mesh sieve to obtain antimony smelting alkaline waste slag powder. Specifically, a jaw crusher is used for crushing, and no grinding media are used. The jaw crusher crushes the slag by compression, avoiding the powder adhesion problems caused by grinding equipment such as vibratory mills. The drying temperature is controlled at 55-65℃; too low a temperature results in low drying efficiency, while too high a temperature may cause a crust to form on the surface of the antimony smelting alkaline waste slag, affecting the uniformity of subsequent mixing. Passing through a 200-mesh sieve ensures uniform powder particle size and improves the uniformity of mixing and sintering.
[0051] Furthermore, the kaolin contains 35-37 wt% alumina and 48-50 wt% silicon dioxide. After grinding the kaolin through a 200-mesh sieve, it is dried at 55-65℃ for 1-2 hours to obtain kaolin powder. Specifically, the alumina and silicon dioxide content in the kaolin directly affects the formation of the mullite crystal phase. If the alumina content is too low, the mullite formation is insufficient, leading to a decrease in refractory mechanical properties; if the silicon dioxide content is too low, there is an excessive glassy phase, which easily causes sintering deformation. Drying removes free water from the kaolin, preventing cracks from forming in the green body during sintering due to moisture evaporation.
[0052] Furthermore, the moisture content of the antimony smelting alkaline waste residue is less than 5 wt%. The ratio of antimony smelting alkaline waste residue to kaolin is 0.5:10 to 5:10 by mass. Specifically, a moisture content of less than 5 wt% in the antimony smelting alkaline waste residue can prevent cracking or foaming of the green body due to violent water vapor volatilization during sintering. The ratio of antimony smelting alkaline waste residue to kaolin is a key parameter affecting refractory performance. When the ratio is 1:10, the fluxing effect of sodium salt is moderate, promoting densification without causing excessive melting; when the ratio is higher than 5:10 (i.e., exceeding 0.5), excessive sodium salt leads to excessive liquid-phase mass transfer, causing the sample to expand, melt, or even liquefy, resulting in a sharp decline in mechanical properties; when the ratio is lower than 0.5:10, the fluxing effect is insufficient, sintering is incomplete, and porosity is high. Therefore, the preferred ratio is 1:10 to 4:10, with 1:10 being the most preferred.
[0053] Furthermore, the mixing is carried out using a mixer for 1 hour. No grinding media or external heating is used during the mixing process, and the mixing temperature is maintained between 15 and 30°C. Specifically, using a mixer instead of a ball mill avoids further pulverization of the powder by the grinding media and powder agglomeration caused by grinding heat. The mixing temperature is controlled within room temperature to prevent the alkaline waste residue from antimony smelting from absorbing moisture or undergoing localized reactions due to temperature rise. A mixing time of 1 hour ensures that the two powders are thoroughly and uniformly mixed; too short a time results in uneven mixing, while too long a time may introduce mechanical impurities.
[0054] Further, the mixture is placed in a mold and pressed under a pressure of 5-20 MPa to obtain a green body. Specifically, when the pressing pressure is below 5 MPa, the green body density is insufficient, resulting in uneven shrinkage after sintering and a tendency to crack; when the pressure is above 20 MPa, the requirements for the mold and press are higher, and it may cause lamellar fracture of the powder. The preferred pressing pressure is 10 MPa. The shape of the green body can be determined according to the target product; for example, a cylinder is used for compressive strength testing, and a cuboid is used for thermal shock resistance testing.
[0055] Further, the green body is sintered at a high temperature to obtain a refractory material; the sintering temperature is 750~1250℃, and the sintering time is 0.5~3 hours. Specifically, when the sintering temperature is below 800℃, kaolin only undergoes dehydroxylation to transform into metakaolinite, without forming a mullite crystalline phase. The sample is chalky, with a loose structure, low mechanical strength, poor solidification of arsenic and antimony, and a still high leaching concentration. When the sintering temperature is between 800~1000℃, the sample begins to partially sinter, but the porosity is still high, and the mullite crystals are incomplete. When the sintering temperature reaches 1200℃, kaolin is completely transformed into the mullite main crystalline phase, the sample has a high degree of densification, and the compressive strength and hardness reach their optimal levels. Arsenic and antimony are effectively solidified in the lattice and glass phase. Although sintering temperatures above 1200℃ can further densify the material, energy consumption increases significantly, and the equipment requirements are higher, resulting in decreased economic efficiency. Therefore, the preferred sintering temperature is 1000~1200℃, with 1200℃ being the most preferred. Sintering times below 0.5 hours result in insufficient reaction; times above 3 hours may cause grain coarsening or over-sintering, increasing energy consumption. The preferred sintering time is 1~2 hours.
[0056] Furthermore, after sintering, the refractory material is cooled to room temperature in the furnace to obtain the refractory material. Specifically, furnace cooling can avoid thermal stress cracks caused by rapid cooling, ensuring the integrity and mechanical properties of the refractory material.
[0057] As an optional option, in the following cases, unless otherwise stated, the main components of the arsenic-alkali slag AAR used are: Na2O 43 wt%, As 22 wt%, and Sb 6 wt%.
[0058] In the following cases, unless otherwise stated, the main contents of kaolin are: 37 wt% alumina and 48 wt% silicon dioxide.
[0059] The main components of the magnesium-rich roasted slag MRS are: MgO 46 wt%, Na2O 8 wt%, As 1.6 wt%, and Sb 0.5 wt%.
[0060] To further illustrate the present invention, the following examples are provided:
[0061] Example 1
[0062] This embodiment provides a method for preparing mullite-phase refractory materials using alkaline waste residue from antimony smelting. The sample obtained is numbered A-10 / 1-1200, and the method specifically includes the following steps:
[0063] Step 1: Weigh 10 g of solid antimony smelting alkaline waste ore (arsenic alkali slag AAR), crush it using a jaw crusher (without grinding media), and dry it in a 60℃ oven until all moisture is evaporated. Grind it thoroughly and pass it through a 200-mesh sieve to obtain antimony smelting alkaline waste ore powder. Weigh 100 g of kaolin, grind it through a 200-mesh sieve, and dry it in a 60℃ drying oven for 1.5 h to obtain kaolin powder. Place the above 10 g of antimony smelting alkaline waste ore and 100 g of kaolin powder (i.e., the mass ratio of antimony smelting alkaline waste ore to kaolin is 1:10) in a mixer and mix for 1 hour. During the mixing process, no grinding media or external heating is used, and the mixing temperature is maintained at room temperature (approximately 25℃) to obtain a mixture. Place the mixture in a mold and press it under a pressure of 15 MPa to obtain a green body (Φ15 mm × 5 mm cylinder).
[0064] Step 2: Place the green billet in a muffle furnace and heat it to 1200℃ at a heating rate of 5℃ / min, holding it at that temperature for 2 hours for sintering. After sintering, cool it to room temperature with the furnace to obtain the refractory material.
[0065] Based on Example 1, the weight ratio of antimony smelting alkaline waste ore, antimony smelting alkaline waste ore, and kaolin, as well as the sintering temperature, were changed, referring to different materials. All samples in this invention are uniformly named according to the following rules:
[0066] The numbering format is: waste residue type code - mass ratio of kaolin to waste residue - sintering temperature.
[0067] In the waste residue type codes, A and ARR represent alkaline waste residue from antimony smelting, M and MRS represent magnesium-rich roasted slag, and K represents pure kaolin (without added waste residue, used as a comparative example). In the mass ratios, 10 / 0 represents pure kaolin without added waste residue, 10 / 0.5 represents a kaolin-to-waste residue mass ratio of 10:0.5, 10 / 1 represents a kaolin-to-waste residue mass ratio of 10:1, 10 / 2 represents a kaolin-to-waste residue mass ratio of 10:2, and 10 / 3 represents a kaolin-to-waste residue mass ratio of 10:3. The sintering temperatures are 800℃, 1000℃, and 1200℃, respectively, and are represented by 800, 1000, and 1200.
[0068] For example: A-10 / 1-1200 represents a sample obtained by sintering alkaline waste residue from antimony smelting, kaolin and waste residue in a mass ratio of 10:1, at 1200℃; M-10 / 0.5-1200 represents a sample obtained by sintering magnesium-rich roasted slag, kaolin and waste residue in a mass ratio of 10:0.5, at 1200℃; K-1200 represents a comparative sample obtained by sintering pure kaolin without adding waste residue at 1200℃.
[0069] In this invention, the alkaline waste residue system for antimony smelting includes the following numbers: A-10 / 0.5-800, A-10 / 0.5-1000, A-10 / 0.5-1200, A-10 / 1-800, A-10 / 1-1000, A-10 / 1-1200, A-10 / 2-800, A-10 / 2-1000, A-10 / 2-1200, A-10 / 3-800, A-10 / 3-1000, and A-10 / 3-1200.
[0070] The magnesium-rich roasted slag system includes the following samples: M-10 / 0.5-800, M-10 / 0.5-1000, M-10 / 0.5-1200, M-10 / 1-800, M-10 / 1-1000, M-10 / 1-1200, M-10 / 2-800, M-10 / 2-1000, M-10 / 2-1200, M-10 / 3-800, M-10 / 3-1000, and M-10 / 3-1200. Among them, M-10 / 0.5-1200 is the optimal sample.
[0071] The pure kaolin comparative examples include the following numbers: K-800, K-1000, and K-1200. Among these numbers, samples with temperature markings (such as -800, -1000, -1200) represent ceramic materials sintered at the corresponding temperatures; samples without temperature markings (such as A-10 / 1) represent unsintered raw mixed powder, while those marked with -RT (such as A-10 / 1-RT) also represent raw powder materials at room temperature.
[0072] In addition, AAR-1200 also refers to A-10 / 1-1200; AAR-1000 also refers to A-10 / 1-1000; and AAR-800 also refers to A-10 / 1-800.
[0073] MRS-1200 also refers to M-10 / 1-1200; MRS-1000 also refers to M-10 / 1-1000; MRS-800 also refers to M-10 / 1-800.
[0074] Comparative Example 1
[0075] Compared to Example 1, the only difference is that an equal weight of clay-based montmorillonite was used instead of kaolinite; all other operations and parameters remained the same as in Example 1. The resulting material was designated Mn-10 / 1-1200. Under high-temperature sintering conditions of 1200℃, montmorillonite is difficult to form the mullite main crystalline phase, and its main phases transform into cordierite and glassy phases. The degree of mullification is significantly lower than that of the kaolinite system. The compressive strength of the obtained sample was only 8.6 MPa, the apparent porosity was as high as 34.5%, and the refractoriness was below 1500℃, which could not meet the requirements for the use of mullite-phase refractory materials.
[0076] Comparative Example 2
[0077] Compared with Example 1, the only difference is that an equal weight of clay sepiolite is used instead of kaolin, while other operations and parameters are the same as in Example 1. Under the high-temperature sintering conditions of 1200℃, sepiolite is mainly transformed into enstatite (MgSiO3) and cristobalite (SiO2), and cannot form mullite phase. The compressive strength of the sample is only 5.2 MPa, and the high-temperature creep resistance is poor, which cannot meet the requirements for the use of refractory materials.
[0078] Comparative Example 3
[0079] Compared with Example 1, the only difference is that an equal mass of industrial-grade alumina and silica mixture (Al / Si ratio the same as in Example 1) was used to replace kaolin. The results showed that the compressive strength of the resulting product was only 52% of that of Example 1, and the apparent porosity was as high as 29%.
[0080] As can be seen from Example 1 and Comparative Example 3, the natural structure of kaolin is conducive to the formation of mullite, resulting in superior performance.
[0081] The refractory material prepared in this embodiment was observed by scanning electron microscopy, X-ray diffraction analysis, and X-ray photoelectron spectroscopy analysis, specifically as follows: Figure 1 , Figure 2 As shown.
[0082] Figure 1The microstructure characterization diagrams are shown for the refractory material prepared in this embodiment and the comparative example (without adding antimony smelting alkaline waste slag under the same process) (K-1200), wherein: Figure 1 (a) and (b) are SEM images (5 µm scale bar) of samples (A-10 / 1-1200, M-10 / 1-1200). Figure 1 (c) is a SEM image of the comparative sample (K-1200) (5 µm scale bar). Figure 1 (d) is the nitrogen adsorption-desorption isotherm for the corresponding sample; Figure 1 (e) is the DFT pore size distribution map of the corresponding sample. Figure 1 Observations (b) and (c) show that the refractory material prepared in this embodiment has a dense structure and very few pores, indicating that the addition of alkaline waste slag from antimony smelting effectively promotes liquid-phase mass transfer and sintering densification; while the comparative sample ( Figure 1 (c) shows a large number of pores and a loose structure. Nitrogen adsorption-desorption test results ( Figure 1 (d) and Figure 1 (e) shows that the BET specific surface area of the sample in this embodiment is much lower than that of the comparative sample, which further confirms the degree of densification of the sample in this embodiment.
[0083] To further investigate the loading forms of arsenic and antimony in refractory materials, X-ray photoelectron spectroscopy (XPS) was used to analyze the samples in this embodiment and the comparative samples. The results are as follows: Figure 2 As shown. Among them, Figure 2 (a) is the high-resolution spectrum of Na 1s. Figure 2 (b) is the high-resolution spectrum of As 3d. Figure 2 (c) is O 1s, Figure 2 (d) is the high-resolution spectrum of Mg 1s. Figure 2 (a) The Na 1s spectrum further confirms the presence of sodium. Figure 2 (b) The As 3d spectrum shows that the arsenic in the sample of this embodiment is mainly in the pentavalent form, with a small amount of trivalent arsenic, indicating that the arsenic is oxidized and stabilized during the high-temperature sintering process. Figure 2 (c) The O 1s spectrum can be fitted to three components, corresponding to Al-O, Si-O and Sb-O bonds respectively, further confirming that antimony enters the ceramic matrix through chemical bonding. Figure 2 The Mg 1s spectrum in (d) confirmed the presence of magnesium, indicating that the magnesium component in the magnesium-rich roasted slag has been successfully incorporated into the refractory material. The XPS analysis results above show that arsenic and antimony exist stably in the mullite lattice or glass phase in the forms of As(V) and Sb-O bonds, respectively.
[0084] Figure 3These are comparative images of the appearance of refractory cylinders prepared at different sintering temperatures (800℃, 1000℃, 1200℃) according to embodiments of the present invention. Figure 3 a represents the arsenic-alkali slag system. Figure 3 b represents a magnesium-rich roasted slag system. (From...) Figure 3 As can be seen, at 800℃, both systems of samples appeared as grayish-white chalky particles with rough and loose surfaces, and no refractory structure was formed. At 1000℃, the arsenic-alkali slag system sample darkened significantly in color and exhibited a glassy luster; the magnesium-rich roasted slag system sample showed less color change, and both systems still had visible pores and loose areas, indicating limited densification. At 1200℃, the arsenic-alkali slag system sample (the sample in this embodiment) had a smooth and dense surface with a uniform grayish-brown refractory luster; the magnesium-rich roasted slag system sample also had a smooth and dense surface, appearing light gray. Neither system showed visible pores or cracks, and both exhibited significant dimensional shrinkage, indicating that liquid-phase sintering was fully carried out at high temperatures, forming a high-density refractory body. The above-mentioned changes in appearance indicate that sintering temperature has a decisive influence on the densification of refractory materials. 800℃ and 1000℃ are insufficient to allow the alkaline waste residue from antimony smelting to fully react with kaolin to form dense refractory materials. Only when the temperature reaches 1200℃ can the fluxing effect of the alkaline oxide components (Na2O and MgO) in the waste residue be fully utilized, and the liquid phase mass transfer between particles is unobstructed, thereby achieving complete sintering.
[0085] Figure 4 This is an XRD phase analysis diagram from an embodiment of the present invention. Wherein, Figure 4 (a) XRD patterns of the 10 / 1 ratio sample at different sintering temperatures (room temperature, 800℃, 1000℃, 1200℃). Figure 4 (b) XRD patterns of arsenic-alkali slag to kaolin clay at 1200℃ after sintering with different mass ratios (10 / 0, 10 / 0.5, 10 / 1, 10 / 2, 10 / 3). Figure 4 (a) It can be seen that the 10 / 1 ratio sample at room temperature exhibits typical diffraction peaks of kaolinite (12.3°, 20.8°, 24.9°, 26.6°), indicating that the kaolinite in the raw material has good crystallinity. After calcination at 800℃, the characteristic peaks of kaolinite are significantly weakened, and the diffraction peaks at 12.3° and 24.9° disappear, indicating that the layered structure of kaolinite undergoes dehydroxylation. At 1000℃, only weak diffraction peaks remain (20.8°, 24.9°, 26.6°), and the intensity of the main peak is reduced by about 50% compared with room temperature, indicating that most of the kaolinite has been transformed into amorphous metakaolinite. At 1200℃, characteristic diffraction peaks of mullite appear (16.4°, 26.3°, 35.2°, 40.8°), indicating that the kaolinite has been completely transformed into mullite. Figure 4(b) It can be seen that the pure kaolinite sample (10 / 0) is dominated by cristobalite as the main crystalline phase, with the strongest peak at 21.6°, accompanied by mullite diffraction peaks (16.4°, 35.2°). With the increase of arsenic alkali slag content, the cristobalite phase gradually disappears, and mullite becomes the main crystalline phase. At the 10 / 0.5 and 10 / 1 ratios, the mullite double peaks (26.6°) are closely overlapping; at the 10 / 2 and 10 / 3 ratios, the double peaks are clearly split, and characteristic diffraction peaks of AlAsO4 appear at 25.5° and 35.6°, indicating that it has entered the coexistence region of mullite and AlAsO4. The characteristic diffraction peak of nepheline (29.1°) was not detected in any of the samples, indicating that Na + It preferentially enters the mullite lattice or glass phase rather than forming nepheline.
[0086] The above results indicate that the Na2O component in arsenic-alkali slag participates in phase evolution at high temperatures. Appropriate addition (10 / 1 or less) can promote the formation of mullite crystal phase, while excessive addition (10 / 2 or more) leads to the precipitation of AlAsO4 phase. The mullite crystal phase gradually forms and tends to be perfect with increasing temperature and optimized ratio, which is the key structural basis for realizing the mechanical properties of refractory materials.
[0087] Example 2
[0088] The compressive strength, thermal shock resistance, apparent porosity, bulk density, and heavy metal leaching concentration of the refractory material prepared in Example 1 were tested and compared with samples of different formulations and sintering temperatures. Details are as follows:
[0089] The antimony smelting alkaline waste residue (arsenic-alkali slag AAR / magnesium-rich roasted slag MRS) used in the experiment had a kaolin mass ratio of 0:10 (pure kaolin), 0.5:10, 1:10, 2:10, 3:10, and 4:10, respectively, and sintering temperatures of 800℃, 1000℃, and 1200℃, respectively. All samples were pressed at a pressure of 10 MPa, and sintered for 2 hours. Specific testing procedures are as follows:
[0090] (1) Tests of apparent porosity and bulk density:
[0091] The boiling method was used for determination. The refractory sample was dried at 110℃ for 2 h, and the dry weight M0 was measured. Then, the sample was placed in boiling water for 2 h, completely submerged, and after cooling, the suspended weight M1 was measured. The sample was removed, the surface moisture was gently wiped off with a damp towel, and the wet weight M2 was measured. Five parallel samples were tested for each group, and the average value was taken. Apparent porosity P was calculated using the formula P=(M2-M0) / (M2-M1)×100%, and bulk density D was calculated using the formula D=M0 / (M2-M1)×ρ (ρ is the density of water, taken as 1 g / cm³). 3 ).
[0092] like Figure 5As shown in (a) and (b), at a sintering temperature of 1200℃, as the AAR ratio increased from 10 / 0.5 to 10 / 1, the apparent porosity decreased significantly and the bulk density increased markedly; however, when further increased to 10 / 2 and 10 / 3, the porosity rebounded and the density decreased, indicating that excessive AAR led to an excessive liquid phase and gas entrainment. The MRS system showed the best densification effect at a ratio of 10 / 0.5 (apparent porosity 4.4%, bulk density 1.75 g / cm³). 3 Further increasing the MRS content also led to an increase in porosity and a decrease in density. In contrast, the samples sintered at 800℃ and 1000℃ showed higher apparent porosity (>25%) and lower bulk density (<1.4 g / cm³). 3 The densification degree is far less than that of the sample sintered at 1200℃.
[0093] (2) Compressive strength test:
[0094] Cylindrical refractory samples (Φ15 mm × 5 mm) were subjected to compression tests using a universal testing machine at a loading rate of 5 mm / min. The maximum load at which the sample fractured was recorded. Five parallel samples were tested for each group, and the average value was taken. The compressive strength was calculated using the formula σ = 4F / (π·D). 2 The calculation is performed, where σ is the compressive strength (MPa), F is the failure load (N), and D is the sample diameter (mm).
[0095] The compressive strength of different formulations at different sintering temperatures was tested, and the results are as follows: Figure 5 As shown in (c). For the AAR system, at a sintering temperature of 1200℃, the 10 / 1 ratio sample had the highest compressive strength, reaching 59.7 MPa; the 10 / 0.5 ratio was second, at 56.9 MPa; the pure kaolin sample (10 / 0) had 52.2 MPa; with further increasing the AAR content, the 10 / 2 and 10 / 3 ratios decreased to 13.7 MPa and 11.6 MPa, respectively. For the MRS system, at 1200℃, the 10 / 0.5 ratio had the highest compressive strength, reaching 65.4 MPa, significantly higher than the optimal value of the AAR system; the 10 / 1 ratio had 56.3 MPa, while the 10 / 2 and 10 / 3 ratios decreased to 16.5 MPa and 14.1 MPa, respectively. The compressive strength of each ratio in both systems at 800℃ and 1000℃ was significantly lower than that of the sample sintered at 1200℃ (both were below 9 MPa), indicating insufficient densification at low temperatures. The above results indicate that alkaline waste residues (AAR and MRS) from antimony smelting can effectively improve the mechanical properties of refractory materials when added in appropriate amounts.
[0096] (3) Linear shrinkage rate test:
[0097] The linear shrinkage rate was calculated using the formula SL=(D1-D2) / D1×100%, where SL is the linear shrinkage rate (%), D1 is the diameter of the cylindrical sample before sintering (mm), and D2 is the diameter of the cylindrical sample after sintering (mm). The diameters of the samples from each embodiment and comparative example were measured before and after sintering using vernier calipers, with each sample measured three times.
[0098] Test results are as follows Figure 5 As shown in (d), for the AAR system, the 10 / 1 ratio sample exhibited the highest linear shrinkage rate of 15.67%, indicating the optimal degree of densification during sintering at this ratio. The 10 / 3 ratio sample showed a negative shrinkage rate of -12.00%, indicating that excessive waste residue caused volume expansion. For the MRS system, the 10 / 0.5 ratio sample showed the highest linear shrinkage rate of 14.37%, while the 10 / 3 ratio sample also showed a negative shrinkage rate of -9.33%. The linear shrinkage rates of all ratios sintered at 800℃ and 1000℃ were below 8%, indicating that effective densification did not occur at low temperatures.
[0099] (4) Thermal shock resistance test:
[0100] A rectangular refractory sample (50 mm × 10 mm × 5 mm) was placed in a muffle furnace and heated to 1100℃. After holding at this temperature for 20 min, it was quickly removed and quenched in room temperature water for 3 min. After removal, it was dried in air for 5 min, which was counted as one thermal cycle. The above cycle was repeated until visible cracks appeared on the sample surface, and the number of cycles was recorded. Three parallel samples were tested for each group of samples, and the average value was taken.
[0101] Experimental results: At a sintering temperature of 1200℃, pure kaolin samples, as well as samples with 10 / 0.5 and 10 / 1 ratios, could withstand more than 10 thermal cycles without cracking. In the 10 / 2 ratio samples, the AAR system cracked after the 7th cycle, while the MRS system cracked after the 6th cycle; in the 10 / 3 ratio samples, both systems cracked after 5 cycles. This indicates that adding an appropriate amount of alkaline waste residue (10 / 1 or less) has no significant negative impact on thermal shock resistance, while excessive addition (10 / 2 or more) will reduce thermal shock resistance, with the MRS system showing a slightly greater decrease than the AAR system.
[0102] (5) Heavy metal leaching concentration test:
[0103] Take 1 g of each sintered sample and place it in 50 mL of deionized water, then seal and soak for 7 days at room temperature. Take the supernatant and determine the concentrations of As(III), total As, and total Sb in the leachate using hydride generation-inductively coupled plasma optical emission spectrometry (HG-ICP-OES). Three parallel samples were tested for each group, and the average value was taken. The leaching experiment was only conducted on the AAR system because the As and Sb contents in the MRS were both less than 1 wt%, and their environmental risk was negligible, so they were not included in the leaching and toxicity assessment.
[0104] Sintering temperature significantly affected the leaching behavior of arsenic. The total arsenic concentrations in the original mixtures of each formulation were relatively high, ranging from 294.3 mg / L (10 / 0.5) to 513.6 mg / L (10 / 3). Figure 6 After sintering at 800℃, the total arsenic concentration decreased to 6.9-20.9 mg / L, but remained at a relatively high level. After sintering at 1200℃, the arsenic leaching concentration decreased significantly, with the lowest concentration in sample 10 / 0.5 at 0.021 mg / L, and no As(III) detected. Samples 10 / 1 and 10 / 2 had concentrations of 0.035 mg / L and 0.135 mg / L, respectively; sample 10 / 3 had a slightly higher concentration of 0.221 mg / L. The As(III) concentration in all samples sintered at 1200℃ was below 0.02 mg / L and negligible. These results indicate that high-temperature sintering can effectively oxidize As(III) to As(V) and stabilize arsenic within the ceramic matrix. In summary, the above-described technical solutions of the present invention are merely preferred embodiments of the present invention and do not limit the patent scope of the present invention. All equivalent structural transformations made using the contents of the present invention's specification and drawings under the technical concept of the present invention, or direct / indirect applications in other related technical fields, are included within the patent protection scope of the present invention.
[0105] Example 3
[0106] The difference from Example 1 is that the particle size distribution of the alkaline waste residue from antimony smelting and kaolin was optimized.
[0107] Antimony smelting alkaline waste ore solids are crushed by a jaw crusher and then passed through 100-mesh and 200-mesh standard sieves to obtain two particle size fractions: a coarse particle size of 100-200 mesh and a fine particle size of less than 200 mesh (<74μm). Similarly, kaolin is crushed by a jaw crusher and then passed through 100-mesh and 200-mesh standard sieves to obtain two particle size fractions: a coarse particle size of 100-200 mesh and a fine particle size of less than 200 mesh (<74μm).
[0108] The refractory material was mixed in a mass ratio of coarse-grained antimony smelting alkaline waste slag: fine-grained antimony smelting alkaline waste slag: coarse-grained kaolin: fine-grained kaolin = 0.5:0.5:5:5 (i.e., the coarse-fine particle gradation ratio was coarse:fine = 1:1) to ensure that the fine particles fully filled the gaps between the coarse particles, thereby increasing the bulk density of the green body. All other process parameters were the same as in Example 1. After sintering, the material was cooled to room temperature in the furnace to obtain the refractory material, denoted as A-10 / 1-1200-G (G represents optimized gradation).
[0109] The performance of the graded optimized sample prepared in this embodiment was tested and compared with that of Example 1 (ungraded, all particles passed through a 200-mesh sieve, with particle sizes ≤74μm). The results showed that the bulk density of the graded optimized sample was approximately 8% higher than that of Example 1, the apparent porosity after sintering decreased from 9.4% in Example 1 to 6.8%, and the bulk density increased from 1.58 g / cm³. 3 Increased to 1.69 g / cm³ 3 The compressive strength increased from 59.7 MPa to 68.4 MPa, an increase of approximately 14.6%. The linear shrinkage rate decreased slightly from 15.7% to 14.9%. The results of Example 3 show that by optimizing the particle size distribution, the overall performance of the refractory material can be further improved without changing the amount of waste residue added or the sintering temperature.
[0110] Example 4
[0111] The difference between this embodiment and Embodiment 1 is that a two-step sintering method is used instead of a one-step isothermal sintering method, and an annealing treatment is added after sintering. The difference in step 2 includes the following steps:
[0112] Step 2-1: Place the green blank obtained in Step 1 in a muffle furnace and heat it to 1100℃ at a heating rate of 5℃ / min, and hold it at that temperature for 0.5 hours;
[0113] Step 2-2: Continue heating at a rate of 5℃ / min to 1200℃, hold for 1 hour to complete the mullite reaction and densification sintering.
[0114] Steps 2-3: After sintering, instead of cooling directly with the furnace, the furnace temperature is lowered to 800℃ and held for 1 hour for annealing. Then, it is slowly cooled to room temperature at a rate of 1℃ / min to obtain the refractory material, denoted as A-10 / 1-1200-TS.
[0115] The samples prepared in this embodiment were subjected to performance tests and compared with those of Example 1 (one-step isothermal sintering followed by furnace cooling). After two-step sintering combined with annealing, the apparent porosity of the samples decreased from 9.4% in Example 1 to 7.2%, and the bulk density decreased from 1.58 g / cm³. 3 Increased to 1.67 g / cm³ 3The compressive strength increased from 59.7 MPa to 66.8 MPa, and the thermal shock resistance increased from 10 cycles to over 15 cycles (1100℃ water quenching cycle). These results demonstrate that two-step sintering and annealing can further improve the mechanical properties and environmental safety of refractory materials without changing the raw material ratio, representing a simple and effective process optimization method.
[0116] The two-step sintering and annealing treatment scheme was applied to the magnesium-rich roasted slag system (M-10 / 0.5-1200-TS). The results showed that the compressive strength of the MRS sample increased from 65.4 MPa to 72.1 MPa, and the apparent porosity decreased from 4.4% to 3.2%. This indicates that the two-step sintering and annealing treatment has a universal performance improvement effect on both waste slag systems.
Claims
1. A method for preparing a mullite-phase refractory material from alkaline waste residue in antimony smelting, characterized in that, Alkaline waste residue and kaolin are mixed in a weight ratio of 0.5:10 to 5:10 and shaped into green blanks. The green blanks are then calcined at a temperature of 750 to 1250°C to obtain the mullite phase refractory material of antimony smelting alkaline waste residue.
2. The method for preparing antimony smelting alkaline waste slag-based refractory material according to claim 1, characterized in that, The alkaline waste residue includes arsenic-alkali residue and / or magnesium-rich roasting residue. The main physicochemical parameters of the arsenic-alkali residue are: Na2O content 42~45 wt%, As content 10~25 wt%, Sb content 2~11 wt%; The main physicochemical parameters of magnesium-rich roasted slag are: MgO content 45~50 wt%, Na2O content 5~15 wt%, As content 0.5~2.0 wt%, and Sb content 0.05~1 wt%.
3. The method for preparing mullite-phase refractory material from antimony smelting alkaline waste as described in claim 1, characterized in that, The kaolin contains 35-40 wt% alumina and 45-50 wt% silicon dioxide.
4. The method for preparing mullite-phase refractory material from antimony smelting alkaline waste as described in claim 1, characterized in that, The particle size of alkaline waste residue and kaolin should be controlled below 100 mesh; Preferably, the alkaline waste residue and kaolin both include large particles and small particles in a weight ratio of 0.5 to 2:1, wherein the particle size of the large particles is 100 to 200 mesh and the particle size of the small particles is less than 200 mesh. The molding method is mechanical pressing, where the pressure of mechanical pressing is 10~20 MPa.
5. The method for preparing mullite-phase refractory material from antimony smelting alkaline waste as described in claim 1, characterized in that, The roasting atmosphere is air, and the roasting time is 0.5 to 3 hours.
6. The method for preparing mullite-phase refractory material from antimony smelting alkaline waste as described in claim 1, characterized in that, The roasting process includes a first roasting process at temperature T1, a second roasting process at temperature T2, and an annealing process at temperature T3. Among them, temperature T1 is 1050~1150℃; temperature T2 is 50~100℃; temperature T3 is 750~850℃; Preferably, the heat preservation time at temperature T1 is 0.4~1h; the heat preservation time at temperature T2 is 0.5~1.5h; and the heat preservation time at temperature T3 is 0.5~1.5h.
7. A mullite phase refractory material made from antimony smelting alkaline waste residue by the preparation method according to any one of claims 1 to 6.
8. The mullite-phase refractory material from antimony smelting alkaline waste as described in claim 7, characterized in that, The refractory material has an apparent porosity of no more than 15%, a compressive strength of no less than 50 MPa, a Mohs hardness of no less than 6, an arsenic leaching concentration of no more than 0.05 mg / L, and an antimony leaching concentration of no more than 0.03 mg / L.
9. The application of a mullite-phase refractory material made from antimony smelting alkaline waste residue according to any one of claims 1 to 6, characterized in that, It is used to prepare refractory materials.
Citation Information
Patent Citations
Process system and method for cooperatively disposing arsenic alkali residues in recycling manner by cement kiln
CN109748526A
Secondary arsenic-alkali residue treatment system
CN211036045U
Lunar and planetary land property allocation method and system
US20020178097A1
Method and mold for molding flexible polymeric envelopes
US20030134067A1